CN? specific turn-on phosphorescent probe with probable application for enzymatic assay and as an imaging reagent - Reddy, Upendar G.; Das, Priyadip; Saha, Sukdeb; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Chemical Communications, 2013)
A new “turn-on” luminescence probe for imaging the uptake of 0.2 ppm inorganic CN− in live HeLa cells as well as for probing the CN− generation through an enzymatic process in a virtual aqueous medium at appropriate pH.